2020
DOI: 10.1364/ol.395202
|View full text |Cite
|
Sign up to set email alerts
|

Portable broadband photoacoustic spectroscopy for trace gas detection by quantum cascade laser arrays

Abstract: We report a portable broadband photoacoustic spectroscopic system for trace gas detection using distributed feedback quantum cascade laser arrays. By sequentially firing 128 lasers, our system acquires a photoacoustic spectrum covering 565 c m − 1 ( 935 − 1500 c m − 1 ) with a normalized-noise-equivalent-absorption coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The average power of the green laser was around 0.2 mW on the sample plane for rhodamine-6G (R6G) associated samples and 30 mW for samples associated with Nile red as the fluorescent reporter. The monolithic QCL included 32 independently addressable wavelength channels in the range of wavenumbers from 1190 to 1330 cm –1 . In typical operation, the QCL array was operated in a burst mode, in which a rapid series of 300 ns laser pulses was sequentially activated firing every 8 μs for “on” cycles ranging from 20 to 250 μs, followed by quiescent “off” periods of equal duration, with an average power of ≤0.8 mW on the sample plane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The average power of the green laser was around 0.2 mW on the sample plane for rhodamine-6G (R6G) associated samples and 30 mW for samples associated with Nile red as the fluorescent reporter. The monolithic QCL included 32 independently addressable wavelength channels in the range of wavenumbers from 1190 to 1330 cm –1 . In typical operation, the QCL array was operated in a burst mode, in which a rapid series of 300 ns laser pulses was sequentially activated firing every 8 μs for “on” cycles ranging from 20 to 250 μs, followed by quiescent “off” periods of equal duration, with an average power of ≤0.8 mW on the sample plane.…”
mentioning
confidence: 99%
“…The monolithic QCL included 32 independently addressable wavelength channels in the range of wavenumbers from 1190 to 1330 cm −1 . 30 In typical operation, the QCL array was operated in a burst mode, in which a rapid series of 300 ns laser pulses was sequentially activated firing every 8 μs for "on" cycles ranging from 20 to 250 μs, followed by quiescent "off" periods of equal duration, with an average power of ≤0.8 mW on the sample plane. Timing details are described in greater detail in the Supporting Information.…”
mentioning
confidence: 99%
“…The mid-infrared (MIR) region lasers may be used, with over two orders of magnitude stronger gas absorption than the visible and near-infrared (NIR) region [17] . With the development of laser technology, various kinds of higher power MIR lasers are applied to increase photoacoustic signal, such as quantum cascade lasers [18] , [19] , interband cascade lasers [20] , [21] and optical parametric oscillators [22] . However, the high cost and maturity of MIR lasers limit their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Vafaie et al 25 used finite element method to solve the coupled photoacoustic equation in gas environment, and analyzed the influence of various effective parameters such as frequency response, quality factor, sound pressure and heat. Liao et al 26 reported a portable broadband PAS detection system for trace gas detection using distributed feedback quantum cascade laser arrays with a noise‐cancel‐absorption coefficient of 2.5×109Wcm1Hz1/2. Dong et al 27 developed a sensitive photoacoustic sensor system for the detection of ppb‐level sulfur dioxide (SO 2 ) using a continuous‐wave room‐temperature high‐power quantum cascade laser (QCL) with an external diffraction grating cavity structure.…”
Section: Introductionmentioning
confidence: 99%